2D Titanium Carbide MXene and Single-Molecule Fluorescence: Distance-Dependent Nonradiative Energy Transfer and Leaflet-Resolved Dye Sensing in Lipid Bilayers - Nicolosi, Valeria (My University, 2024)
Despite their growing popularity, many fundamental properties and applications of MXene materials remain underexplored. Here, the nonradiative energy transfer properties of 2D titanium carbide MXene are investigated and their application in single-molecule biosensing is explored for the ﬁrst time. DNA origami positioners are used for single dye placement immobilized by a speciﬁc chemistry based on glycine-MXene interactions, allowing precise control of their orientation on the surface. Each DNA origami structure carries a single dye molecule at predetermined heights. Single-molecule ﬂuorescence confocal microscopy reveals that energy transfer of an organic emitter (ATTO 542) on transparent thin ﬁlms made of spincast Ti 3 C 2 Tx ﬂakes follows a cubic distance dependence, where 50% of energy transfer eﬃciency is reached at 2.7 nm (d0 ). MXenes are applied as short-distance spectroscopic nanorulers, determining z distances of dye-labeled supported lipid bilayers fused on MXene’s hydrophilic surface. Hydration layer (2.1 nm) and lipid bilayer thickness (4.5 nm) values that agree with the literature are obtained. These results highlight titanium carbide MXenes as promising substrates for single-molecule biosensing of ultrathin assemblies, owing to their sensitivity near the interface, a distance regime that is typically inaccessible to other energy transfer tools
Keywords: MXene materials; DNA origami positioners; single-molecule biosensing; MXene materials; DNA origami positioners; single-molecule biosensing